DESKRIPSI KEPEMIMPINAN KEPALA DESA GAPURA KECAMATAN WATUKUMPUL KABUPATEN PEMALANG - Sulistiyo, Heru (Jurnal Politik Pemerintahan Dharma Praja, 2019)
Leadership Description of the Head of the Gapura Village, Watukumpul District, Pemalang Regency. The practice of democracy has legitimized village leadership through village head elections. This legitimacy is a social asset that strengthens the village head to lead the village. Although in practice the implementation of government duties is certainly not enough if it only relates to public recognition, it requires administrative capabilities. At the concept and theory level, sometimes the village head cannot define in detail and measurably, but basically the nature of leadership values has been taken with simple patterns. Therefore, a combination of the two is needed so that the wheels of government can be implemented properly. The purpose of this study was to find out the leadership of the village head, to provide input to the District Head and Pemalang District Government about the leadership of the village head, and to provide an empirical picture to the readers as material for the study of governmental science development. This study uses a descriptive approach to describe existing phenomena, both natural and human engineering. The results show that at the empirical level the leadership values have been largely carried out by the Head of the Gapura Village, but the concepts of leadership in theoretical studies are still needed in addition to regulatory guidelines to complement the capacity of a village head